1986
DOI: 10.3904/kjim.1986.1.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Serum Uric Acid in Essential Hypertension

Abstract: In order to observe the relationship of hyperuricemia and essential hypertension, we studied serum uric acid in 139 patients with essential hypertension visiting the Department of Internal Medicine, Pusan National University Hospital, between May 1982 and July 1983, and analyzed its values in terms of various clinical and laboratory parameters.The mean concentration of serum uric acid and incidence of hyperuricemia in essential hypertension were 6.60 ± 1.96 mg%, 57.9% and those of the normal control group were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Serum uric acid (UA) levels were demonstrated to be an independent predictor for developing hypertension [ 5 - 7 ]. Regardless of the different ethnic origins, a continuous relationship between serum UA and blood pressure (BP) was observed in African-Americans and whites [ 8 , 9 ] as well as in Asians [ 7 , 10 ] including Koreans [ 11 - 13 ]. For determining the causal role of serum UA in the development of hypertension, Mazzali et al [ 14 ] demonstrated an elevation in serum UA followed by an increase in BP via a crystal-independent mechanism in rat models.…”
Section: Introductionmentioning
confidence: 99%
“…Serum uric acid (UA) levels were demonstrated to be an independent predictor for developing hypertension [ 5 - 7 ]. Regardless of the different ethnic origins, a continuous relationship between serum UA and blood pressure (BP) was observed in African-Americans and whites [ 8 , 9 ] as well as in Asians [ 7 , 10 ] including Koreans [ 11 - 13 ]. For determining the causal role of serum UA in the development of hypertension, Mazzali et al [ 14 ] demonstrated an elevation in serum UA followed by an increase in BP via a crystal-independent mechanism in rat models.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Irrespective of the different ethnic origins & regions, a certain association between serum UA and blood pressure (BP) has been seen in African-Americans and whites 8,9 as well as in the Asians 7,10 including Koreans. [11][12][13] In the study of causal role of serum UA in the development of hypertension, Mazzali et al 14 observed an elevation in the levels of serum UA followed by an increase in BP via a crystal-independent mechanism in rat models. Further it has also been found that reduction of serum UA was associated with a decrease in BP through the regulation of renin-angiotensin and nitric oxide system.…”
Section: Introductionmentioning
confidence: 99%